Mechanical strength of antibiotic-loaded PMMA spacers in two-stage revision surgery - Lunz, André; Knappe, Kevin; Omlor, Georg; Schonhoff, Mareike; Renkawitz, Tobias; Jäger, Sebastian (BMC musculoskeletal disorders, 2022)
Antibiotic-loaded polymethylmethacrylate (PMMA) bone cement spacers provide high local antibiotic concentrations and patient mobility during the interim period of two-stage revision for periprosthetic joint infection (PJI). This study compares mechanical characteristics of six dual antibiotic-loaded bone cement (dALBC) preparations made from three different PMMA bone cements. The study`s main objective was to determine the effect of time and antibiotic concentration on mechanical strength of dALBCs frequently used for spacer fabrication in the setting of two-stage revision for PJI.
Gesehen am 09.02.2023